Experimental evaluation of analgesic activity of Naga Parpam: An Siddha formulation - V, Shalini; A, Mariappan; G, Senthilvel; R, Meenakumari (International Journal of Membrane Science and Technology, 2023)
Background : Prolonged usage of NSAIDs and corticosteroids was associated with serious side effects. Siddha is an ancient system of medicine, promotes the utilization of herbal anad elemental formulations. Interestingly, certain elements considered toxic in modern medicine, such as Arsenic (As), Cadmium (Cd), Mercury (Hg), Iron (Fe), Silver (Ag), Gold (Au), etc., have been employed in Siddha herbo mineral formulation for the treatment of illness, a practice that dates back to ancient times. Introduction Pain is a widely recognized indicator of poor health, the analgesic medications are employed to alleviate it. In Siddha classics, pain is considered a separate disease called Soolai. Naga Parpam is one of the herbo metal preparations with analgesic potential but no scientific evaluation there. Aim: To evaluate the analgesic activity of Naga parpam in experimental rats using Tail immersion method. Materials and methods : After obtaining permission from the IAEC, the animals were separated into 5 groups of 6 animals Each Group 1 (control) received ghee orally, and Group 2 (standard) received Pentazocine in dose 10 mg/kg intraperitoneally. The test drug Naga parpam was mixed with the adjuvant Ghee and administrated per oral route to three groups (Group 3,4,5), Group 3 (test) received Naga Parpam in low dose 6 mg/kg, Group 4 (test) received mid dose 12 mg/kg, Group 5 (test) received high dose – 24 mg/kg ). Statistical analysis : One-way ANOVA followed by the Dunnett test P < 0.05 was considered to be significant. Results : The test drug Naga parpam has significant analgesic activity in the tail flick method (P <0.01) by increasing the reaction time of the rats. Conclusion : The present study indicates that the test drug Naga parpam possesses significant central analgesic activity in the tail flick method.